Primary Systemic Amyloidosis: A Case Report - Saurav Sen Oli; Abhishek Jha; Anisha Karki; Shova Sapkota; Laxman Adhikari (Journal of Nepal Medical Association, 2023)
Primary systemic amyloidosis is a systemic disease characterised by the deposition of misfolded proteins extracellularly in different organs without any known cause in the background, eventually leading to multiorgan dysfunction and death. The incidence of primary amyloidosis is estimated at 5.1-12.8 cases per million, with a poor prognosis. We report a case of a 69-year male with lower back pain, shortness of breath, and anasarca diagnosed as primary systemic amyloidosis by serum-free light chain assay and kidney needle biopsy. He was started on intravenous bortezomib and dexamethasone. Though he adhered to his medications, with time he developed renal insufficiency marked by azotemia following which hemodialysis was performed. Primary systemic amyloidosis is a rare clinical condition with a very poor prognosis. Further studies are needed to understand the proper pathophysiology and treatment of the disease.